ANALISIS PERILAKU DAN PREFERENSI KONSUMEN TERHADAP PEMBELIAN PRODUK MADU DI PROVINSI JAWA TENGAH PADA MASA PANDEMI COVID-19 - Umma Rizqi Marfu’ah; Darsono Darsono; Isti Khomah (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2023)
The COVID-19 pandemic has made people realize the importance of maintaining a healthy body. A healthy body with a good immune system is believed to reduce the risk of transmission of covid 19. One product that is believed to have health benefits is honey, so it is needed and much sought after during the pandemic. This study aims to find out the attributes of honey products that are consumer preferences, and to find out the attributes that consumers consider the most in purchasing honey products in Central Java during the Covid-19 pandemic. The basic method used is the descriptive method. The research location was chosen purposively, namely in Central Java Province. Sampling was done by using accidental sampling of as many as 100 respondents. Data analysis used descriptive analysis, the Chi-Square method, and Fishbein Multi-attribute. The results showed that the attributes that become consumer preferences are brands that have been registered and have legal protection, medium volume (250ml-500ml), glass bottle packaging, high price (>Rp50,000.00/250ml packaging), and thick viscosity level. The attributes that consumers consider the most in their decision to purchase honey products in Central Java during the Covid-19 pandemic, respectively, are the level of viscosity, packaging, price, brand, and volume